Localized fat or adiposity: therapeutic classification: Localized fat classification - Vega López, Petra (Aesthetic Medicine, 2023)
White adipose tissue is essential for energy storage, endocrine communication, and insulin sensitivity. However, its distribution may present some alterations, as is the case of localized adiposity made up of normal adipose tissue, which is one of the conditions that represent the highest demand in aesthetic medicine. The most common causes for its development are an increased caloric intake and decreased energy demand due to a sedentary lifestyle. Localized adiposity is usually chronic and progressive; treatment therefore requires a substantial learning curve from a team of healthcare professionals. In addition, it can significantly impact the patient and lead to important psychological problems. The traditional classification of localized adiposity involves several measurements: a) waist circumference, measured at the midline level between the costal margin and the iliac crest; b) hip circumference, measured at the level of the greater trochanters of the femur. Based on these measurements and other considerations for diagnosing and classifying localized adiposity, we have developed an algorithm that includes the following criteria: i) body mass index; ii) adipose tissue location; iii) degree of alteration of the underlying tissues; iv) aesthetic impact on body harmony; v) level of emotional discomfort it causes the patient. This algorithm aims to help determine the best therapeutic approach for each patient. It identifies five types of localized adiposity, with three subtypes, depending on their location.